Associations of perfluorooctane sulfonate alternatives and serum lipids in Chinese adults. (October 2021) - Cong, Jianping; Chu, Chu; Li, Qing-Qing; Zhou, Yang; (Min) Qian, Zhengmin; Dee Geiger, Sarah; Vaughn, Michael G.; Zeng, Xiao-Wen; Liu, Ru-Qing; Hu, Li-Wen; Yang, Bo-Yi; Chen, Gongbo; et al.
Highlights: Few studies have explored the associations between Cl-PFESAs and serum lipids. A large population-based study was conducted in China to assess these associations. Perfluorooctane sulfonate alternatives were adversely associated with serum lipids. That such associations were similar to those between legacy PFASs and TC. Abstract: Background: Chlorinated polyfluorinated ether sulfonic acids (Cl-PFESAs), a group of perfluorooctane sulfonate (PFOS) alternatives, can be widely observed in humans and environmental matrices. However, associations between exposure to Cl-PFESAs and serum lipid levels in adults are unknown. Objective: To explore the relationships between Cl-PFESA levels and serum lipid levels in adults. Methods: We analyzed 1238 adults from the Isomers of C8 Health Project, a cross-sectional study conducted in China from July 2015 to October 2016. The average age of the participants was 61.98 ± 14.40 years. We quantified two select legacy per- and perfluoroalkyl substances [perfluorooctanoic acid (PFOA) and PFOS] and their alternatives (6:2 and 8:2 Cl-PFESAs). We also measured four serum lipids: low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and triglycerides (TG). We used generalized linear models to estimate the associations between PFASs and serum lipids, with PFASs defined as either a categorical variable divided into quartiles or as a continuous variable. Results: We found that 6:2 Cl-PFESA was positively associated with serum TC and LDL-C. For instance, LDL-C levels in the highest quartile of 6:2 Cl-PFESA exposure (Q4) were significantly higher than those in the lowest quartile (Q1) [β: 0.19, 95% confidence interval (CI): 0.08, 0.30]. Further analysis showed that one ln-ng/mL increase in 6:2 Cl-PFESA exposure corresponded to a 0.10 mmol/L (95% CI: 0.05, 0.16) LDL-C increase, and that exposure to 8:2 Cl-PFESA was negatively correlated with HDL-C (β: −0.03, 95% CI: −0.05, −0.01). TC had a similar relationship with both 6:2 Cl-PFESA and legacy PFASs. Participants with a BMI ≥ 25 kg/m 2 exhibited a stronger association between 6:2 Cl-PFESA and TC. Conclusions: Our findings make the novel suggestion that exposure to Cl-PFESAs are adversely associated with serum lipid levels, and that such associations are also observed in legacy PFASs. Increased investigation into the effects of Cl-PFESAs exposure on human health is warranted.